2018
DOI: 10.1007/s10067-018-4326-5
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody and metalloproteinase activity in early arthritis

Abstract: Objectives The aim of the study was to evaluate the frequency of anti-mutated citrullinated vimentin antibodies (a-Sa), anticitrullinated α-enolase peptide 1 antibodies (a-CEP-1), anti-filaggrin antibodies (AFAs), heterogeneous nuclear ribonucleoprotein compies/anti-RA33-antibodies (a-hnRNP/RA33), anti-carbamylated protein antibodies (a-CarP), and metalloproteinase (MMPs) activity in patients with early inflammatory arthritis (EIA). Methods Seventy-four patients with EIA: 51 diagnosed with RA (rheumatoid arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Therefore, an inconsistent antigen source may adversely affect the capability for detection of the anti-CEP 1 antibody and the diagnostic performance of home-made ELISA kits. Of note, although the meta-regression showed that 3 factors may contribute to the heterogeneity, the subgroup analysis did not explore the no- [15][16][17][20][21][22]31,34,35,37,38 The results were significantly different due to variations in sample size, study design or patient ethnicity, so further study is needed to investigate the reasons for these variations. Additionally, the first presentation of the anti-CEP antibody can be earlier than the increase in the anti-CCP antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, an inconsistent antigen source may adversely affect the capability for detection of the anti-CEP 1 antibody and the diagnostic performance of home-made ELISA kits. Of note, although the meta-regression showed that 3 factors may contribute to the heterogeneity, the subgroup analysis did not explore the no- [15][16][17][20][21][22]31,34,35,37,38 The results were significantly different due to variations in sample size, study design or patient ethnicity, so further study is needed to investigate the reasons for these variations. Additionally, the first presentation of the anti-CEP antibody can be earlier than the increase in the anti-CCP antibody.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33][34][35]37,38 Most of the studies used ELISAs to detect the anti-CEP 1 antibody by commercial ELISA kits or a self-established ELISA method. [15][16][17]19,22,24,25,28,29,[31][32][33][35][36][37][38] Two types of CEP-1 peptide sequences were used as coating antigens in the self-established ELISA methods: one was a CKIHA(cit)EIFDS(cit)GNPTVEC (cyclic) with C-terminal and N-terminal cysteines to facilitate cyclization in 6 included studies, 25,31,33,35,37,38 and another was a KIHA(cit)EIFDS(cit) GNPTVE without cysteine in 4 of the studies. 24,28,29,32 Detailed...…”
Section: Study Characteristics and Literature Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что ММП-3 отражает активность РА и позволяет прогнозировать развитие эрозий [54,55]. Высокий уровень ММП-3 у АЦЦП-негативных пациентов с недифференцированным артритом может быть преди ктором развития РА (ДЧ=63,6%; ДС=81,5%) [56,57].…”
Section: иммунологическая характеристикаunclassified